Wealth Effects and the New Economy - Sloek, Torsten; Edison, Hali. (Washington, D.C. : International Monetary Fund, 2001)
This paper investigates if there is a different impact from changes in "new" and "old" economy stock valuations on private consumption. Estimating a reduced-form VAR for seven OECD countries for the 1990s, it is found that the impact from changes in old economy stock valuations on consumption is in general larger in the United States, Canada, and United Kingdom than in continental Europe. Furthermore, the impact from changes in new economy valuations to consumption is roughly the same in the United States, Canada, and United Kingdom and in continental Europe. Finally, the results suggest that in continental Europe the impact on consumption from changes in the valuation of new economy stocks is bigger than from the old economy stocks, whereas for the United States, Canada, and United Kingdom the impact is more or less the same between the two sectors.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet